2021
DOI: 10.21203/rs.3.rs-137855/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Science-Policy Framework for a Green Economic Recovery After the COVID-19 Pandemic

Abstract: As current production and consumption patterns of humanity exceed planetary boundaries, many opinion leaders have stressed the need to adopt green economic stimulus policies in the aftermath of the COVID-19 pandemic. Here, we provide an integrated multi-stakeholder framework to design an economic recovery strategy aligned with sustainability objectives. We first employ quantitative energy and economic models and then design a multi-criteria decision process in which we engage social actors from government, ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The study's findings suggested that health protocols and automation should be included in policy design as drivers for supply chain sustainability. In a post-pandemic setting, Zachariadis et al (2021) proposed a comprehensive model for a green economic recovery that is tied to long-term sustainability goals. The findings of the study emphasize the trade-off among environmental and economic objectives.…”
Section: Effects Of Covid-19 On Freight Transportationmentioning
confidence: 99%
“…The study's findings suggested that health protocols and automation should be included in policy design as drivers for supply chain sustainability. In a post-pandemic setting, Zachariadis et al (2021) proposed a comprehensive model for a green economic recovery that is tied to long-term sustainability goals. The findings of the study emphasize the trade-off among environmental and economic objectives.…”
Section: Effects Of Covid-19 On Freight Transportationmentioning
confidence: 99%
“…The results from the study suggest policy development considering health protocols and automation as the drivers for long-term sustainability in SC. Also, Zachariadis et al (2021) proposed an integrated framework for a green economic recovery associated with the sustainability objectives in a post-pandemic environment. The results from the study highlight the trade-off between environmental and economic objectives.…”
Section: Literature Reviewmentioning
confidence: 99%